THE SIGNIFICANCE OF SOCIAL SPACE IN VERTICAL NEIGHBOURHOODS IN MALAYSIA - S. Abdullah; H. Ahmad (Journal of Islamic, Social, Economics and Development, 2022)
Vertical neighbourhood is a new housing terminology that is closely linked to the socio-economic, political, neighbourhood and environment to create an integrated, stable and thriving neighbourhood community. In a vertical neighbourhood, the community always desires to participate in cultural, recreational, and religious practices in order to improve their quality of life in residential areas. However, the development process emphasizes only on the quantity aspect of housing rather than the community social aspects. Hence, this paper will focus on the significance of social spaces in the vertical neighbourhood in Malaysia. To conduct this study, content analysis of housing publications was used. Content analysis is a research method of analysing text-based data sets to identify the frequency of keywords and phrases and to discern patterns with the data. Total of 38 articles were analysed to identify keywords; The outcome of this paper revealed that there are certain features that may influence social interaction in the vertical neighbourhood among the community. Other than that, the study also found that the need for social space in a vertical neighbourhood is important and cannot be ignored to avoid decreasing social interaction between communities.